Virtual breakout rooms: An effective approach to offer guidance to medical students on residency applications - Filler, Tali; Pieris, Dilshan; Teitelbaum, Daniel; Chaya, Nader; Park, Stephanie; Majeed, Safa; Premji, Laila (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Implication statementPeer mentorship on residency applications has been difficult due to recent public health measures, prompting a shift from in-person events to virtual platforms. To address gaps in career exploration, we created a virtual, non-recorded space that allowed medical students and residents to discuss the Canadian Resident Matching Service (CaRMS) process meaningfully and transparently. Attendees reported a greater understanding of the match process and reduced anxiety after the event. This model provides a virtual framework that can be adapted for various mentorship opportunities.